Researching the Ends of Identity: Birth and Death on Social Media - Leaver, Tama (Sage, 2015)
This paper argues that expanding the scope of social media studies to examine birth and early life at one end, and death and memorialisation at the other, demonstrates that social media is never just about an individual, but also the way individuals are always already joined together as families, groups, communities and more. Mapping these ends of identity also reveals more of the nuances of everyday social media use and its impact.